Ability composition in the class and the school performance of immigrant students - Elena Meschi; Caterina Pavese (Global Labor Organization (GLO), 2023)
Using longitudinal data from the Italian National Institute for the Evaluation of the Education System (INVALSI), this paper investigates whether the ability of classmates affects the educational attainment of immigrant students. We focus not only on the average quality of peers in the class, but we further investigate which part of the ability distribution of peers drives the effect, by assessing the role played by the extreme tails of the ability distribution. Our empirical strategy addresses students' endogenous sorting into classes by exploiting the within-student across-subjects variation in achievements and the simultaneity problem by using predetermined measures of peers' ability. We show that peers' ability matters. While native students are mostly influenced by the average quality of their peers, immigrant children are detrimentally affected by the fraction of very low achievers in the classroom. Our findings provide valuable guidance to policymakers concerning the allocation of students to classes in order to foster immigrant students' integration and learning.
Keywords: J15; I21; 330; Peer effects; Immigrant students; Education